Wood-Based Biomass Energy Development for Sub-Saharan Africa : Issues and Approaches - World Bank (World Bank, Washington, DC, 2017)
Nearly half the world's population and about 81 percent of Sub-Saharan African (SSA) households rely on wood-based biomass energy (fuel wood and charcoal) for cooking. This degree of reliance is far greater than in any other region. While the use of biomass fuels in China, India and much of the developing world has peaked or will do so in the near future, SSA's consumption will either remain at very high levels or even grow over the next few decades. Population growth, coupled with strong urbanization dynamics and relative price changes of alternative fuels, offset the important achievements made over the past decade by significant investments in energy access, rural and urban electrification, off-grid energy developments, and the promotion of alternative energy sources. With increasing economic development, the demand for energy is increasing as well and consumers depend on a broader portfolio of energy sources to satisfy growing energy needs. While electricity and other energy sources are needed to satisfy additional energy needs emerging with economic development, a vast majority of Sub-Saharan African consumers continue to use wood based biomass energy for cooking. Especially electricity is not regarded a suitable alternative for cooking given equipment and use costs. Biomass burning in cook stoves also emits black carbon (BC) as part of visible smoke, which is particulate matter that results from incomplete combustion. Climate science now views BC as the second or third largest warming agent after carbon dioxide, alongside methane. In the case of biomass cooking, the warming effects of BC and the cooling effects of organic carbon that is also emitted during the burning appear to be closely balanced. Given the present uncertainty about the net impact, additional research is currently underway. Black carbon has also an impact at the regional level: it accelerates melting of ice and snow, and contributes to regional pollution which can alter climatic conditions and precipitation patterns over a wide area. This paper advocates that any policy reform should entail a combination of clear rules, transparent enforcement, strong incentives and awareness-creation/capacity development. Key stakeholders and the general public need guidance by way of information campaigns, training, and demonstration projects to ensure that awareness-deficits or false perceptions do not curtail policy implementation. The bureaucratic and administrative barriers e.g. overcomplicated forest management planning requirements, complex fiscal systems and land tenure procedures may inhibit development and thus warrant critical reflection. The regulatory framework needs to integrate externalities in order to promote adequate pricing of charcoal, and thus enhance regional economies.